2010
DOI: 10.1093/abbs/gmq006
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes BCG-induced maturation of human dendritic cells

Abstract: Dendritic cells (DCs) are important for the initiation of the adaptive immune response against Mycobacterium tuberculosis. Autophagy is an innate and adaptive defense mechanism and important for the control of M. tuberculosis. However, the role of autophagy in the adaptive immune response against M. tuberculosis remains to be determined. In the present study, we studied the effects of autophagy on the maturation of DCs infected with Bacillus CalmetteGuérin (BCG). The phenotype and function of the DCs were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…In our previous study, we showed that Earle's balanced salts solution (EBSS), a saline solution with physiological pH which is often used to induce autophagy, enhances BCG-induced DC maturation via the up-regulation of CD86, HLA-DR, and IL-6 [6]. In the present study, we found that EBSS and rapamycin differentially regulated the maturation of human DCs.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…In our previous study, we showed that Earle's balanced salts solution (EBSS), a saline solution with physiological pH which is often used to induce autophagy, enhances BCG-induced DC maturation via the up-regulation of CD86, HLA-DR, and IL-6 [6]. In the present study, we found that EBSS and rapamycin differentially regulated the maturation of human DCs.…”
Section: Introductionmentioning
confidence: 59%
“…6). Our previous data demonstrated that the LC3-II level was increased when THP-1 cells were treated with different ratios of EBSS, with 12.5% and 25% EBSS enhancing the LC3-II level in BCG-infected THP-1 cells [6]. Collectively, these results indicate that rapamycin and EBSS enhance the activity of autophagy in BCG-infected THP-1 cells.…”
Section: Rapamycin Inhibited the Maturation Of Bcg-infected Dcsmentioning
confidence: 73%
See 1 more Smart Citation
“…As such, the level of p62 should decrease with increased autophagic flux, while a block in autophagosome maturation will lead to p62 accumulation (Kuma et al , 2007). Treatment of THP-1 cells with chloroquine (CQ), which is known to block autophagosomal maturation (Chiu et al , 2009, Min et al , 2009), led to the expected increase in both the conversion of LC3B-I to LC3B-II, and accumulation of p62 (Fig. 4B).…”
Section: Resultsmentioning
confidence: 94%
“…Transcriptomic assessment of these monocytes by microarrays and pathway analysis revealed specific clusters of genes significantly induced by β-glucan training with an intriguing signal found in the ubiquitin-related proteins and associated catabolic processes (Figure 1a). Since ubiquitination plays an important role in autophagy [8], a process that has previously been shown to improve intracellular processing of BCG [9], [10], we examined the role of autophagy in the induction of trained immunity.…”
Section: Resultsmentioning
confidence: 99%